Skrining Fitokimia dan Aktivitas Penyembuhan Luka Bakar Ekstrak Etanolik Morinda Citrifolia L. pada Kulit Kelinci (Oryctolagus Cuniculus) - Retno Priamsari, Margareta; Auly Yuniawati, Noor (Jurnal Farmasi (Journal of Pharmacy), 2019)
Burns are damage to the unit or network components caused by changes in temperature, chemicals, electricity, and radiation. Alkaloid, flavonoid, saponin, and tannin compounds in Noni leaves (Morinda citrifolia. L) have the potential to heal burns. The aim of this study was to determine phytochemical screening and the activity of noni leaf extract to the healing of burns on rabbit skin. This type of research is experimental with a randomized pattern design in one direction. Noni leaf ethanolic extract was obtained by remaseration method using 96% ethanol solvent and phytochemical screening tests. Tests of burns were carried out on 5 male New Zealand strain rabbits. Each part of the rabbit's back skin was divided into 5 treatments, namely positive control (Bioplacenton gel), negative control (vaselin flavum), and ethanolic extract of noni leaf concentrations of 10%, 15%, and 20%. The skin of the back is induced by a 2 cm diameter hot metal plate for 10 seconds until a shallow second degree burn occurs. Burn wound healing parameters include visual observation of physiological mean and reduction in wound diameter for 21 days. The average percentage of wound healing was analyzed by non-parametric statistics with Kruskal-Wallis, followed by Mann-Whitney with a confidence level of 95%. The results showed that the ethanolic extract of noni leaves contained alkaloids, flavonoids, saponins and tannins as well as having burn healing activities. The variation in the concentration of ethanolic extract of noni leaves is 10%; 15% and 20% have no significant effect on the healing of burns.